Kebijakan Hukum Dalam Sektor Umkm Sebagai Penggerak Ekonomi Nasional - Novita Anggie Sihombing (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the existing legal policies supporting the development of Micro, Small, and Medium Enterprises (MSMEs) as a driver of the national economy. MSMEs play a crucial role in job creation, poverty reduction, and enhancing economic competitiveness. Despite various government policies to promote MSMEs, such as easing licensing and access to financing, this sector still faces numerous challenges, including legal obstacles that hinder development. This research uses the literature study method to gather information from relevant sources, aiming to identify effective legal policies and propose improvements. The study results indicate that more responsive legal policies and better coordination between stakeholders can enhance the effectiveness of MSME support. Legal policy reform based on the real needs of MSMEs is necessary to strengthen their contribution to the national economy.